Recurrent Cases of Periprosthetic Joint Infection Caused by Staphylococcus Aureus: Reinfection or Reactivation of a Pathogen? - Andrey A. Kechin; Victoria S. Borobova; Taalaibek U. Sheraliev; Svetlana O. Chretien; Irina N. Tromenshleger; Vitaliy V. Pavlov; Maxim L. Filipenko (Travmatologiâ i Ortopediâ Rossii)
Background. Staphylococcus aureus is one of the most common pathogens causing periprosthetic joint infection (PJI). Despite the high genetic diversity of S. aureus strains, determining phylogenetic relationships and, consequently, the source of infection is a challenging task that can only be addressed through detailed comparison of the genomes of the obtained isolates.